Effects on Serum Fractalkine by Diet and Omega-3 Fatty Acid Intervention: Relation to Clinical Outcome - Kristian Laake; Ingebjørg Seljeflot; Morten Wang Fagerland; Ida Unhammer Njerve; Harald Arnesen; Svein Solheim (Mediators of Inflammation)
Introduction. Fractalkine is a chemokine associated with atherosclerosis. Increased serum levels have been reported in unstable coronary artery disease (CAD) and to predict mortality in heart failure. Mediterranean-like diet and omega-3 fatty acids (n3-PUFA) have documented cardioprotective and anti-inflammatory effects. We have investigated the effect of Mediterranean-like dietary counseling and n-3 PUFA on serum fractalkine in an elderly population and its ability to predict cardiovascular disease (CVD). Materials and Methods. 563 men (age 64–75 yrs) at high risk of CAD were randomized into a 2 × 2 factorial designed trial for 3-year dietary counseling and/or n-3 PUFA supplementation (2.4 g/d). Circulating levels of fractalkine were measured at baseline and at end of study. Clinical events were recorded after 3 years. Results. Fractalkine levels were significantly reduced in all groups from baseline to 3 years (P<0.001, all), but without between-group differences in changes. Fractalkine levels at baseline were not predictive for CVD events (n=68) or total mortality. Lower fractalkine levels were observed in smokers (P=0.019). Conclusions. Reduced levels of fractalkine from baseline to 3 years were observed, however, without any influence of Mediterranean-like diet or n-3 PUFA supplementation. Fractalkine levels at baseline were not predictive for later CVD events.